Merumuskan Kerangka Aksioma Etik Islam - Faradis, Jauhar (Literasi: Jurnal Ilmu Pendidikan, 2009)
Islamic ethic is representation of axioms that includes four elements namely, unity, equally, independent and responsibility. Ethics also meets all the principal characteristics of the axiom system: minimal, consistent, and independent. The device of this axiom also reflects the central message of the Islamic social philosophy is refusing of the status quo that is not fair and the demands of social change.  Analysis used in this chapter is the use of  ethical  beliefs  in  a  typical  Muslim community  as a  valid  logical  basis  of  economic behavior.Key words: Naqvi, Initiating, Economics, Islam.